MOTIVASI MANAJEMEN LABA DALAM KAPITALISASI BIAYA RISET DAN PENGEMBANGAN - MARIADI, YUSLI; SUTRISNO, SUTRISNO; ROSIDI, ROSIDI (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2012)
The capitalization of research and development (RD) costs is a controversial accounting issue because of the contention that such capitalization is motivated by incentives to manipulate earnings. Indonesian Financial Accounting Standards (SAK) allows for the capitalization of RD costs. Based on a sample of manufacturing companies of Indonesia Stock Exchange from 2009 to 2011, this study examines whether companies’ decisions to capitalize RD costs are affected by earnings-management motivations such as earnings smoothing and to avoid violating debt-covenant. In addition, this study aims to show that the capitalization of RD costs affects the level of firms’ earnings-management. Using a Tobit regression model to test the first and second hypotheses and linear regression model to test third hypotheses, the results show that the companies do capitalize the RD costs for earnings-smoothing and reducing the risk of violating debt-covenants purposes. In addition, the results show that the capitalization of RD cost affects the level of firms’ earnings-management and it is a part of earnings management.